Rhodesia : Crisis of Color - Edited by Theodore Bull, Introduction by Gwendolen M. Carter (Chicago Quadrangle Books, 1967)
Mr. Bull, editor of the Central African Examiner (one of Salisbury's leading magazines before it ceased publication late in 1965 as a result of rigid censorship bye the Rhodesian government), presents the first authoritative explanation of Rhodesian situation.
Include appendix, bibliography and index.
Introduction by Gwendolen M. Carter
Keywords: Zimbabwe -- Politics and government -- Economic history